Atmospheric dispersion modelling for regulatory purposes in the United Kingdom. (4th August 2014) - Timmis, R.J.
Short–range atmospheric dispersion models are used to assess the environmental impact of airborne pollutants from industrial plants. The results are of interest to a range of specialist and non–specialist groups, including regulators, operators, environmental organisations, and local residents. In order that these groups can be well–informed, it is important to develop clear and consistent procedures for presenting and evaluating dispersion calculations. Her Majesty's Inspectorate of Pollution regulates the most potentially polluting industrial plants in England and Wales. Examples are given of how practical regulatory decisions can be clarified by good design and presentation of dispersion calculations. The examples cover (a) graphical comparisons of 'new' and 'old' generation models, (b) development of a flowsheet for evaluating discharge stack heights, and (c) use of decision–tree charts to plan a control strategy for multiple–source impacts of nitrogen dioxide.